If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(3x + 5) = 5 Reorder the terms: 5x(5 + 3x) = 5 (5 * 5x + 3x * 5x) = 5 (25x + 15x2) = 5 Solving 25x + 15x2 = 5 Solving for variable 'x'. Reorder the terms: -5 + 25x + 15x2 = 5 + -5 Combine like terms: 5 + -5 = 0 -5 + 25x + 15x2 = 0 Factor out the Greatest Common Factor (GCF), '5'. 5(-1 + 5x + 3x2) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(-1 + 5x + 3x2)' equal to zero and attempt to solve: Simplifying -1 + 5x + 3x2 = 0 Solving -1 + 5x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -0.3333333333 + 1.666666667x + x2 = 0 Move the constant term to the right: Add '0.3333333333' to each side of the equation. -0.3333333333 + 1.666666667x + 0.3333333333 + x2 = 0 + 0.3333333333 Reorder the terms: -0.3333333333 + 0.3333333333 + 1.666666667x + x2 = 0 + 0.3333333333 Combine like terms: -0.3333333333 + 0.3333333333 = 0.0000000000 0.0000000000 + 1.666666667x + x2 = 0 + 0.3333333333 1.666666667x + x2 = 0 + 0.3333333333 Combine like terms: 0 + 0.3333333333 = 0.3333333333 1.666666667x + x2 = 0.3333333333 The x term is 1.666666667x. Take half its coefficient (0.8333333335). Square it (0.6944444447) and add it to both sides. Add '0.6944444447' to each side of the equation. 1.666666667x + 0.6944444447 + x2 = 0.3333333333 + 0.6944444447 Reorder the terms: 0.6944444447 + 1.666666667x + x2 = 0.3333333333 + 0.6944444447 Combine like terms: 0.3333333333 + 0.6944444447 = 1.027777778 0.6944444447 + 1.666666667x + x2 = 1.027777778 Factor a perfect square on the left side: (x + 0.8333333335)(x + 0.8333333335) = 1.027777778 Calculate the square root of the right side: 1.013793755 Break this problem into two subproblems by setting (x + 0.8333333335) equal to 1.013793755 and -1.013793755.Subproblem 1
x + 0.8333333335 = 1.013793755 Simplifying x + 0.8333333335 = 1.013793755 Reorder the terms: 0.8333333335 + x = 1.013793755 Solving 0.8333333335 + x = 1.013793755 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.8333333335' to each side of the equation. 0.8333333335 + -0.8333333335 + x = 1.013793755 + -0.8333333335 Combine like terms: 0.8333333335 + -0.8333333335 = 0.0000000000 0.0000000000 + x = 1.013793755 + -0.8333333335 x = 1.013793755 + -0.8333333335 Combine like terms: 1.013793755 + -0.8333333335 = 0.1804604215 x = 0.1804604215 Simplifying x = 0.1804604215Subproblem 2
x + 0.8333333335 = -1.013793755 Simplifying x + 0.8333333335 = -1.013793755 Reorder the terms: 0.8333333335 + x = -1.013793755 Solving 0.8333333335 + x = -1.013793755 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.8333333335' to each side of the equation. 0.8333333335 + -0.8333333335 + x = -1.013793755 + -0.8333333335 Combine like terms: 0.8333333335 + -0.8333333335 = 0.0000000000 0.0000000000 + x = -1.013793755 + -0.8333333335 x = -1.013793755 + -0.8333333335 Combine like terms: -1.013793755 + -0.8333333335 = -1.8471270885 x = -1.8471270885 Simplifying x = -1.8471270885Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.1804604215, -1.8471270885}Solution
x = {0.1804604215, -1.8471270885}
| 5=5a | | 12rs+5r-6s= | | x^2-490x+5000=0 | | 5+4b=20 | | 9-6x=26 | | 3y-2=5y+6 | | -3(4+6n)-7=8n-7-14 | | -5n-6+4n=-14 | | -6(y-2)=2y-24 | | -6(7-2)=2y-24 | | 6=2+d | | -5u-46=-8(u+8) | | Y-2=2.6(x-0) | | 45-(4-2y-4(y+7))=-4(1+3y)-(4-3(y+2)-2(2y-5)) | | -11+x=-7x-8(x+1) | | -37+7=-9y+49 | | -37+7=-97+49 | | 10x-30+7x=13x | | 13-3v=8v+2 | | -5v+8(v+3)=39 | | 7x^2+16x=192 | | 3(w-8)+3w=-18 | | 18n-24t= | | 7=3y+y-8 | | 6(y+3)+2y=-38 | | X-2+x-3=123 | | 6x-9x+9=x-7+16 | | (2-z)(2z+5)=0 | | (t+33)+(t+11)=4t-9 | | 12-4y=6 | | s-4t=29 | | 4(6+2x)=2(x-3) |